Theories of matter - editor A. Solomon; co-editors M. Balkanski; H.-R. Trebin (World Scientific, 1994)
This volume contains a selection of articles on modern theoretical physics contributed by scientists. It is dedicated to Joseph L. Birman for his contribution to the field. The topics covered are condensed matter and solid state physics, elementary particles and quantum optics